Structural and immunological characterization of Friend murine leukaemia virus glycopolypeptide using synthetic oligopeptides. - Bayer, H (1984)
Using terminal position, hydrophilicity, predicted reverse turns and type specificity as criteria, five oligopeptides were selected for synthesis from the amino acid sequence of the envelope glycopolypeptide gp70 of Friend murine leukaemia virus. These peptides corresponded to the amino acids 6-12 (pep1), 124-131 (pep2), 256-262 (pep3), 283-290 (pep4) and 434-441 (pep5). After coupling to carriers, bovine serum albumin or keyhole limpet hemocyanin, antisera were prepared in rabbits. All of the five oligopeptides were immunogenic and pep1, pep2, pep4 and pep5 were able to elicit antibodies to the native glycopolypeptide. These sequence-specific antisera distinguished between glycoproteins of different leukaemia viruses. At least three of the selected peptides, the type-specific oligopeptides pep3, pep4 and pep5, were found to be natural epitopes of gp70.